1988
DOI: 10.1227/00006123-198803000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Disorders Associated with von Recklinghausen's Neurofibromatosis: A Case Report

Abstract: A 28-year-old woman with von Recklinghausen's neurofibromatosis (NF-1) had a huge hematoma in the left posterior nuchal region. Carotid and vertebral angiograms revealed marked stenosis at the C3 portion of the left internal carotid artery, slight moyamoya staining, occlusion of the left vertebral artery at the atlas level, and a right internal carotid artery aneurysm. The radiographic, clinical, and histological features of this case are discussed together with a review of 42 similar cases found in the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 0 publications
0
56
0
2
Order By: Relevance
“…Occlusion of the posterior vessels as presented in our case is much less frequent. Among 37 cases of occlusive cerebrovascular disorder reviewed by Sobata et al, only six had involvement of the posterior circulation 10 . Extracranial involvement of the carotids and vertebral arteries has also been described 5 .…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Occlusion of the posterior vessels as presented in our case is much less frequent. Among 37 cases of occlusive cerebrovascular disorder reviewed by Sobata et al, only six had involvement of the posterior circulation 10 . Extracranial involvement of the carotids and vertebral arteries has also been described 5 .…”
Section: Discussionmentioning
confidence: 96%
“…Sobata et al reviewed the cases of cerebrovascular disorders associated with NF1 and found 33 cases of stenotic/occlusive arterial disorder, six cases of intracranial aneurysm, and four cases with both stenotic/occlusive disorder and aneurysm 10 . Stenotic/occlusive disorder of intracranial vascular supply generally presents symptoms in childhood or adolescence, being eventually the first manifestation of NF1 in children 11 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations